PENERAPAN HAK ANGKET DEWAN PERWAKILAN RAKYAT PASCAAMANDEMEN UNDANG-UNDANG DASAR REPUBLIK INDONESIA TAHUN 1945 - RINDAWAN, I KETUT (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â In the Constitution according to the 1945 Constitution of the Republic of Indonesia, the House of Representatives (DPR) as a legislative body has a position parallel to the executive. The position of the House is strong and can not be dissolved by the president. The House of Representatives as a legislative body has the right and function of supervision over the course of government. Supervision functions are required in order to check and balance (supervise and balance) and to prevent abuse of power.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Efforts to empower the House to be more independent from the influence of executive power began in the reform era. Empowerment of Parliament can be seen from the use of rights and functions of Parliament. The House's efforts are seen with the use of interpellation rights, the right of inquiry, and the right to express opinions that are part of the oversight function. In this case, the topic of discussion in this research is How to Implement the Right of Inquiry of House of Representatives After the Constitution of the 1945 Constitution?Â Â Â Â Â Â Â Â Â Â Â Â Â Â Accept it, this research uses descriptive analysis method by using deductive mindset that operational at start from exposure about aspect of law of right of inquiry of House of Representatives post-amendment. This is based on the consideration that this research seeks to find the rule of law and legal theory on the use of the right of inquiry in the Indonesian state administration systemThe cornerstone of the exercise of the right to inquiry in the Indonesian state administration system is contained in Law No. 6 of 1954 concerning the determination of the right of inquiry of the House of Representatives and Number 27 of 2009 concerning the structure and position of the People's Consultative Assembly, the DPR, DPD and DPRD is a reprimand to the government by investigating violations, violations committed by the government which subsequently conducted deliberations to decide the outcome.Â Â Â Â Â Â Â Â Â Â Â Â Â Â So the conclusion of the results of this study finds that the right to inquiry is very important because, in the policy-making process, governments often take unilateral policies without consideration of members of the House of Representatives, and even controversial policies between the government and the House of Representatives are also common. Thus, the existence of the right of inquiry can pave the way for DPR to investigate government policies that are suspected to be contradictory to the prevailing laws and regulations.Â Keywords: Rights of Questionnaire, Parliament, Post-Constitution of the 1945 ConstitutionÂ Â ABSTRAKÂ Dalam ketatanegaraan menurut UUD Republik Indonesia tahun 1945, Dewan Perwakilan Rakyat (DPR) sebagai lembaga legislatif mempunyai kedudukan sejajar dengan lembaga eksekutif. Kedudukan DPR kuat serta tidak dapat dibubarkan oleh presiden. DPR sebagai lembaga legislatif mempunyai hak dan fungsi pengawasan terhadap jalannya pemerintahan. Fungsi pengawasan diperlukan dalam rangka check and balance (mengawasi dan mengimbangi) serta untuk mencegah terjadi penyalahgunaan kekuasaan.Upaya pemberdayaan DPR agar lebih mandiri dari pengaruh kekuasaan eksekutif diawali pada era reformasi. Pemberdayaan DPR dapat dilihat dari penggunaan hak maupun fungsi DPR. Upaya DPR terlihat dengan penggunaan hak interpelasi, hak angket, dan hak menyatakan pendapat yang merupakan bagian fungsi pengawasan. Dalam hal ini yang menjadi topik pembahasan dalam penelitian ini adalah Bagaimana Penerapan Hak angket DPR Pascaamandemen Undang-Undang Dasar Tahun 1945?Berkenan dengan itu, maka penelitian ini menggunakan metode analisis deskriptif dengan menggunakan pola pikir deduktifÂ yang operasionalnya di mulai dari pemaparan tentang aspek hukum hak angket Dewan Perwakilan Rakyat pascaamandemen. Hal ini didasarkan pada pertimbangan bahwa penelitian ini berupaya untuk menemukan aturan hukum dan teori hukum tentang penggunaan hak angket dalam sistem ketatanegaraan IndonesiaLandasan pelaksanaan hak angket dalam sistem ketatanegaraan Indonesia termuat dalam Undang â?? undang Nomor 6 tahun 1954 tentang penetapan hak angket Dewan Perwakilan Rakyat dan Nomor 27 Tahun 2009 tentang susunan dan kedudukan MPR, DPR, DPD, dan DPRD, merupakan teguran kepada pemerintah dengan menyelidiki pelanggaran-pelanggaran yang dilakukanÂ pemerintah yang selanjutnya dilakukan musyawarah untuk memutuskan hasilnya.Â Â Â Â Â Â Â Â Â Jadi simpulan hasil dari penelitian ini menemukan bahwa hak angket sangat penting karena, dalam proses pengambilan kebijakan, pemerintah sering mengambil kebijakan sepihak tanpa pertimbangan anggota Dewan Perwakilan Rakyat, dan bahkan kebijakan kontroversi antara pemerintah dan Dewan Perwakilan Rakyat juga sering terjadi. Sehingga dengan adanya hak angket dapat membuka jalan bagi DPR untuk menyelidiki kebijakan-kebijakan pemerintah yang diduga bertentangan dengan peraturan perundang- undangan yang berlaku.Â Kata Kunci: Hak Angket, DPR, Pascaamademen UUD 1945